Analysis of The Influence of Transformational Leadership and Organizational Commitment on Employee Performance - Gunanjar, Imam; Maulidan, Rahmat; Syahputra, Rico; Verinanda, Muhammad Ridwan; Saputra, Ryanda; Maharani, Riantari (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the influence of transformational leadership and organizational commitment on the performance of PT Asra Banda Aceh employees. This study uses a quantitative approach with a type of causal associative research. The population in this study is all employees of PT Asra Banda Aceh, with a sampling technique using a saturated sampling method so that as many as 75 respondents were obtained. Data collection was carried out through a questionnaire with a Likert scale. The data analysis technique uses multiple linear regression with the help of statistical software. The results of the study show that partially transformational leadership and organizational commitment have a positive and significant effect on employee performance. Simultaneously, these two variables also had a significant effect on employee performance with a determination coefficient value (R²) of 0.68. This suggests that 68% of employee performance variations can be explained by transformational leadership and organizational commitment, while the rest are influenced by other factors outside of the study. This study concludes that transformational leadership and organizational commitment are important factors in improving employee performance. Therefore, organizations need to develop an inspiring leadership strategy and strengthen employee commitment to achieve optimal and sustainable performance..